Strategies for realizing a sakinah family in the context of families with careers: Challenges and solutions - Aisyah, Rina Nur; Weber, Marcus (AS-SAKINAH, 2024)
This study examines effective strategies in realizing a sakinah family in the midst of increasingly complex career demands. The main problems faced by career families include limited time for family, role conflict between work and family responsibilities, and lack of social support. The purpose of this study is to identify these challenges and formulate solutions that can be applied to achieve a balance between professional and family life. The research method used was a combination of in-depth interviews and a survey of 25 families with careers in various major cities in Indonesia. The data obtained was analyzed to understand the dynamics of career families and find strategies that have been successfully applied in everyday life. The results showed that efficient time management, open communication, and fair division of roles in the household are key elements in maintaining family harmony. The use of technology has also emerged as an innovative solution that helps career families manage domestic tasks and stay connected effectively. In addition, religious and cultural values, such as spirituality and mutual cooperation, play an important role in strengthening family bonds and creating a harmonious environment.